0475 Validation of Portable Monitor Testing for Diagnosis of Obstructive Sleep Apnea in COPD Patients. (27th April 2018) - Xu, L; Chang, Y; Han, F; Keenan, B T; Kneeland-Szanto, E; Pack, A I; Kuna, S T
Abstract: Introduction: Current clinical practice guidelines recommend in-laboratory polysomnography (PSG) to diagnose obstructive sleep apnea (OSA) in patients with comorbities due to lack of evidence supporting the use of portable monitor testing. Our aim was was: to evaluate the performance of a type 3 portable monitor (Nox-T3, Nox Medical, Inc) used for home sleep apnea testing (HSAT) to diagnose OSA in patients with COPD.#8232; Methods: Ninety-two COPD patients (88.0% males, mean ± standard deviation age 66.5 ± 7.8 years, body mass index 27.6 ± 5.8 kg/m2, FEV1/FVC 53.6% ± 12.6%, FEV1/[predicted FEV1] 54.1 ± 18.6%) underwent overnight, unattended HSAT with the portable monitor followed by an overnight in-laboratory PSG with simultaneous portable monitor recording. All portable monitor recordings were scored using automated analysis and then manually edited. The PSGs were scored based on recommended guidelines. Results: When scoring of hypopneas required a ≥ 4% oxygen desaturation event, the mean ± standard deviation apnea-hypopnea index (AHI) was 16.7 ± 20.6 events/h on HSAT, 20.2 ± 23.3 events/h on in-laboratory portable monitor recording, and 23.0 ± 29.1 events/h on PSG ( P < .0001). Bland-Altman analysis of AHI on HSAT versus PSG showed a mean difference (95% confidence interval) of −6.78 (−10.23, −3.34); limits of agreement (equal to ± 2 standard deviations) was −39.53 to 25.96 events/h. Based on a threshold AHI ≥ 5 events/h for diagnosis of OSA, HSAT had 93% sensitivity, 78% specificity, 88% positive predictive value, and 86% negative predictive value compared to PSG. Using a threshold AHI ≥ 15 events/h, HSAT had 75% sensitivity, 98% specificity, 97% positive predictive value, and 83% negative predictive value. Closer agreements were present when comparing the simultaneous PSG and in-lab portable monitor recordings. Conclusion: Despite known differences between HSAT and PSG, the results show close agreement between the two diagnostic tests in COPD patients, especially when controlling for night-to-night variability and changes in sleeping environment.#8232; Support (If Any): NIH HL094307, Beijing Municipal Science & Technology Commission No. Z161100002616012.